Overview of empirical equation prediction for ultimate axial load of precast lightweight foamed concrete sandwich panel (PLFP) - Goh, Wan Inn; Abdul Samad, Abdul Aziz; Mohamad, Noridah; Abdullah, Redzuan (Asian Research Publishing Network (ARPN)., 2016)
In the absence of analytical theory, empirical equation is useful in estimating the ultimate load carrying capacity of structural component. Empirical approach means the collection of data on which to base a theory or derive a conclusion in science. It is part of the scientific method. The empirical method is often contrasts with the precision of the experimental method where data are derived from an experiment. This paper review the development of empirical equation from solid reforced panel to sandwich panel. The previous developed empirical equations are be able to predict an adequate ultimate strength of PLFP panel under axial loading due to the safety factor reduction. Series of experiment and Finite Element ANALYSIS (FEA) were carried out to produce sufficient data to analyze the previous developed empirical equation to predict the ultimate load carrying capacity. From findings, a new empirical equation is in need to predict the ultimate axial load of sandwich panel in order to get accurate prediction